Zooplankton diversity and distribution in a deep and anoxic Mediterranean coastal lake - KEHAYIAS, G.; RAMFOS, A.; IOANNOU, S.; BISOUKI, P.; KYRTZOGLOU, E.; GIANNI, A.; ZACHARIAS, I. (Mediterranean Marine Science, 2013)
The variation of the smaller size fraction of zooplankton was investigated during a two-year period in a brackish deep and anoxic coastal lake of western Greece (Aitoliko), along with the specific environmental characteristics of this ecosystem. The zooplanktonic community comprised a relatively small number of taxa and it was dominated by brackish-water calanoid copepods (Paracartia latisetosa, Calanipeda aquaedulcis) and in certain periods by rotifers and tintinnids. The zooplankton abundance showed an increase in the warmer period starting from late spring and reached maximum values in July. In the well oxygenated surface layer, temperature was the most important parameter influencing the seasonal cycles of all groups. In contrast, the oxygen depletion a few meters under the surface affected the vertical distribution of most of the zooplankton groups, which were found restricted in the surface layer especially from spring until autumn. Only the meroplanktonic larvae of polychaetes presented increased proportions in the deeper layers. Salinity has not significantly influenced the zooplanktonic assemblages. The results point out the degraded status of the Aitoliko basin where the hypoxic/anoxic layers resulted to a high portion of dead organic material identified as copepod carcasses, and underlines the necessity of monitoring of this ecosystem.